Review article: investigation and management of internal fistulae in Crohn's disease. Issue 10 (15th March 2021) - Tjandra, Douglas; Garg, Mayur; Behrenbruch, Cori; McCormick, Jacob; Simkin, Paul; Prentice, Ralley; Trinh, Andrew; Al‐Ani, Aysha; Vaughan, Rose; Macrae, Finlay; Christensen, Britt
Summary: Background: Crohn's disease is an inflammatory, penetrating intestinal disease associated with fistula formation. Fistulae in Crohn's disease can be classified into external and internal fistulae. Internal fistulae form between the gastrointestinal tract and another internal organ and include enteroenteric, enterocolic, enterovesical and rectovaginal fistulae. They are associated with significant morbidity and a decreased quality of life. Aim: To review the classification, diagnosis, medical and surgical management of internal fistulae in Crohn's disease, and propose a treatment algorithm. Methods: A literature review on internal fistulae in Crohn's disease in the adult population was undertaken, synthesised and summarised. Results: Internal fistulae occur in up to 15% of patients with Crohn's disease. Multi‐modal assessment including a combination of endoscopy and cross‐sectional imaging, usually magnetic resonance, is required to diagnose fistulae and determine extent of disease. Determining optimal treatment strategies for these complex fistulae remains a challenge due to limited and generally low‐quality data. Most studies to date have focussed on luminal disease, with (usually post hoc) outcomes more often reported for external fistulae, particularly perianal fistulae, than internal fistulae. Anti‐tumour necrosis factor therapies have emerged as the mainstay of medical therapy, with particularly promising data for enterovesical fistulae, but many patients will still require surgical intervention. The indications and optimal timing of surgery vs medical therapy remains uncertain; thus multi‐disciplinary input when making such decisions is important. Conclusions: Internal fistulae result in significantly increased morbidity in Crohn's disease, and further studies to determine optimal multi‐modality management strategies incorporating medical and surgical therapy are required. Abstract : The optimal management of internal fistulae associated with Crohn's disease remains uncertain. There is little evidence to guide treatment. Current data favour anti‐TNFα agents as the most effective medical therapy. Multi‐disciplinary engagement is imperative.